Measurement of muscular Christian ideals in sport: Validation of the Contemporary Muscular Christian Instrument. (March 2020) - Meyer, Andrew R; Wynveen, Christopher J; Watson, Nick
Muscular Christianity's influential role in establishing Western sport values and ideals during the 19th century has long been acknowledged by sport scholars. Yet these relatively dated sets of physical moral constructs are rarely understood as having lasting relevance, or as forming part of the contemporary attraction to sport, and thus have been missing in critical sociological analyses of sport. While shown to be valid and reliable, initial results from developing the Contemporary Muscular Christian Instrument (CMCI) also suggested that modifications to item wording could enhance readability and capture all six theorized factors of muscular Christianity, supported by literature. The current scale development study is aimed to strengthen the instrument and verify its structural validity and internal consistency among a more diverse sample population: spectators at the 2014 Tour de France. Following data collection and cleaning of data, a confirmatory factor analysis was conducted, and internal consistencies were examined. Results indicate strong support for the structural validity of the revised 20-item, 6-factor CMCI, showing strong factor loadings across all items and acceptable internal consistencies for all six-theorized factors. Findings among this international sample of sport spectators suggest that historic muscular Christian themes used to develop this instrument continue to shape and influence perceptions of what is deemed good, right, and valuable in sport. Our findings point to the importance of understanding these six moral constructs as contemporary discussions on the social value and importance of such activities evolve. The revised CMCI provides sociologists of sport a tool by which to examine theorized muscular Christian constructs, promoting certain values about sport and its social "good, " and allows for further investigation into sports' social significance, meanings, and values within related topics. This paper details the improvements to the survey instrument, the CFA results, and recommendations for future application and research using the survey instrument.